Recreation Value of Fri Estate - an Application of Travel Cost Method - Gera, Mohit; Mohan, Giresh; Bisht, N. S. (Indian Forester, 2005)
FRI estate spread over an area of around 450 ha in the sylvan surroundings of the Doon valley offers opportunities for recreation not only to the local population but also to the tourists from far off places. The estate is visited by 55-60,000 visitors on an average per year. The FRI main building, an impressive edifice of the Greco-Roman and Oriental architecture spread over a plinth area of 2.5 ha, with the outer Himalayas forming its backdrop is the main attraction for the visitors. This colonial era piece of architecture is probably the most photographed building in the Dehra Dun city. The building houses six forestry museums, a Xylarium with 18,000 specimens and a world class herbarium with 3,30,000 specimens. The study was carried out to estimate recreational benefits; the society derives from the FRI estate by application of Travel Cost Method. A recreational value of Rs. 27.10 per visit was obtained and when extrapolated to the total number of visitors, the recreational benefits from FRI estate have been estimated to be Rs. 16,26,190/-.